BATAVIAASCHE PLANTEN EN DIERENTUIN: KEMUNCULAN GAGASAN KONSERVASI SATWA MELALUI KEBUN BINATANG OLEH ELITE BATAVIA 1864 -1942 - Irmalasari, Fitri R. (Puslitjakdikbud Balitbang Kemdikbud, 2016)
AbstractThis article talks about the emergence of Bataviaasche Planten en Dierentuin (BatavianBotanical and Zoological Garden) in 1864 as the first zoological park in Batavia aswell as in East Dutch Indies. It becomes the first Dutch East Indies ex-situ conservation(conservation of plants and/ or animals which was done outside their natural habitat),that was spearheaded by a handful of elite Batavia. The science development in the 19thcentury and political ideology of the Dutch Colonial were the backgrounds of the changingperspective of Batavian well-educated elites towards nature environment and its sourcesincluding animals. Data sources which are the annual reports of the zoo organisation,photographs, travel notes, will disclose the motive and aim as well to necessarily attestthe power of social construction, namely race and social class, as the main driver of theemerging conservation notions and the importance of knowledge on animals for Bataviancitizens from the 19th to early 20th century. The presence of an artificial habitat of plantsand animals in the capital of colonial land, after all, was a microcosm that representedthe change of people’s attitude, which is from traditional to modern, as comprehended byBatavian elites in managing animals. AbstrakArtikel ini membahas kemunculan Bataviaasche Planten en Dierentuin (Kebun Botanidan Binatang Batavia) pada 1864 sebagai kebun binatang pertama di Batavia maupundi Hindia Belanda. Kebun binatang tersebut menjadi konservasi ex-situ (konservasitumbuhan dan/ atau satwa yang dilakukan di luar habitat alaminya) pertama di HindiaBelanda dan dipelopori oleh segelintir elite Batavia. Perkembangan ilmu pengetahuanpada abad ke-19 serta ideologi politik pemerintah kolonial melatarbelakangi perubahancara pandang elite terpelajar Batavia terhadap lingkungan alam beserta isinya, termasuksatwa. Sumber data artikel ini berupa laporan-laporan tahunan pengelola kebun binatang,foto-foto, catatan-catatan perjalanan, yang akan memperlihatkan motivasi dan tujuan parapenggagasnya serta dengan sendirinya menunjukkan kekuatan konstruksi sosial beruparas dan kelas sosial sebagai penggerak utama atas lahirnya gagasan-gagasan mengenaikonservasi dan pentingnya pengetahuan mengenai satwa bagi masyarakat Batavia sejakabad ke-19 hingga awal abad ke-20. Kehadiran sebuah habitat buatan bagi tumbuhandan satwa bernama kebun binatang di ibu kota koloni, bagaimanapun merupakan sebuahmikrokosmos yang merepresentasikan perubahan sikap, yang oleh elite Batavia dipahamisebagai transisi dari sikap masyarakat tradisional ke masyarakat modern dalam mengatursatwa.